Pengaruh Content Marketing, Brand Image dan E-WOM (Electronic Word of Mouth) Terhadap Keputusan Pembelian Moisturizer Skintific (Studi Kasus Pada Mahasiswa FEB UNISMA Pengguna Aplikasi Shopee) - Angely, Mely; Asiyah, Siti; Primanto, Alfian Budi (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
Abstract This research aims to determine the influence of content marketing, brand image and e-WOM (electronic word of mouth) on the decision to purchase skintific moisturizer. The location of this research is by distributing questionnaires on several platforms such as Instagram, Tiktok, and Whatsapp. This research is quantitative research. This research uses a case study method where data is obtained by distributing questionnaires using Google Form to Unisma Feb students who use the Shopee application who are selected using purposive sampling. Determining the sample size used the Malhotra formula and the results obtained were 80 respondents. The data analysis techniques used in this research are the multicollinearity test, heteroscedasticity test, multiple linear regression analysis, F test, T test and coefficient of determination test with data processing using SPSS software. Keywords : Purchasing decisions, Content marketing, Brand image and E-WOM (electronic word of mouth)